MIGRASI INTERNASIONAL, JAMINAN PERLINDUNGAN, DAN TANTANGAN EKONOMI GLOBAL - Abdul Haris (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
The setback of regional economic growth, in turn, has a big enough influence in the regional labor market. This condition is deteriorated by the decrease of investment flow as a consequence of the existing political rush and it has a direct impact toward the economic field. The reality that the political virus has transformed and even nearly destroyed the national and regional economic structures becomes an inevitable thing. The fact that the economic pressure incomparable with the economic potency of the country of origin becomes one of important determinants for the rise of new dimensions in migration activities. It is also pushed by the development of globalization spirit which has direct consequence in economic field of some countries. Therefore, in the next era of global transparency and free market, government in many countries (including countries in the third world) can no longer shoot aside on behalf of any political interests or economic protections but open a political entrance to give a more transparent security commitment to their labors in general.